ACUAN PEMBELAJARAN PERMAINAN SOFTBALL MODEL TGfU - Agus Susworo Dwi Marhaendro (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2008)
This article discusses Teaching Games for Understanding (TGfU) model, particularly on the striking and fielding classification. It begins with the meaning of striking/fielding games, which includes attacking activities by striking, batting, kicking, or hitting the ball, and also such activities as catching and throwing the ball as a result of the hitting, striking, or kicking. Another name of this game is run-scoring games, which means a game done by running in order to score. Furthermore, this article also presents the components which are noteworthy in the teaching and learning striking/fielding games. The games that can be classified as striking/ fielding games are softball, baseball, rounder, cricket, kickball, and kasti. This article focuses more on softball rather than other striking/fielding games. The reference in teaching softball is in line with striking/fielding games teaching framework covering the tactical problems and the level. Teaching model for softball should closely pay attention on these tactical problems, which are: scoring and also levels of complexity, from simple to more complex, to the real game. Kata kunci: acuan, pembelajaran, permainan softball